A Supply Selection Method for better Feasible Solution of balanced transportation problem. (1st October 2022) - Amaliah, Bilqis; Fatichah, Chastine; Suryani, Erma
Highlights: Transportation Problem (TP) is delivering the product from supply to demand. Initial Basic Feasible Solution (IBFS) influences the optimal solution of TP. Supply Selection Method (SSM) is proposed to find the IBFS. SSM selects the cell with the largest allocation, if the differences are same. SSM satisfies the First Least Cost, if the supply is same. Abstract: Transportation Problem (TP) is correlated with product distribution between supply locations and demand locations. TP aims to minimize the total transportation cost, and TP is one of the most important challenges in optimization. To solve the TP, Initial Basic Feasible Solution (IBFS) is a crucial step to determine the Optimal Solution. However, some developed methods of IBFS do not always produce a good initial solution. This study uses a new method called Supply Selection Method (SSM), which is proposed to the get better initial solution for balanced TP. It was compared with other IBFS methods, including Vogel's Approximation Method (VAM), Juman Hoque Method (JHM), Total Opportunity Cost Matrix – Minimal Total (TOCM-MT), and Bilqis Chastine Erma method (BCE) to evaluate the performance. The new method was examined with 45 total cases consisting of 31 cases from some journals, 4 cases generated randomly, and 10 samples of real data from XYZ company. The study results show that SSM provided a better initial basic solution than other methods, with 41 of 45 cases reached the Optimal Solution. The evaluation shows that SSM provided more outcomes with lower total minimal cost than LCM, VAM, JHM, TOCM-MT, and BCE.